Inventory And Documentation For Bebali Mask Dance - Sustiawati, Ni Luh; Sariada, I Ketut (Institut Seni Indonesia Denpasar, 2020)
The objective of this research is to describe the kinds and the function of Bebali mask dances in each regency or municipality in Bali province and the perception of the public about them. This research was conducted in 9 districts / cities in Bali, namely Jembrana, Buleleng, Tabanan, Badung, Denpasar, Gianyar, Klungkung, Bangli and Karangasem, each represented by the two villages that develop the Bebali Mask dance. This research intended to expose a phenomenon, therefore it applies the phenomenological qualitative approach. It was chosen due to the consideration that this research is focused upon action or activity by one or more people related to the making of inventory and documenting the Bebali mask dance in Bali province, by classifying the kinds and functions of Bebali mask dances and by uncovering the perception of the public concerning the Bebali mask dance in the regencies/municipalities in Bali. The result shows that almost all instances of Bebali mask dance, especially the Pajegan variety, is connected with religious rituals, such as the Dewa Yadnya, Resi Yadnya, Pitra Yadnya, Manusa Yadnya, and Bhuta Yadnya. The Bebali mask dance in the province of Bali symbolizes the cycle of human life which can be described as a circle where life rotates naturally. The mask dance contains an ideal of how to live a life, that is to strike a balance between the adoration of the Divine and compassion and duty to fellow men and love of nature, which in Hindu philosophy is called â€œTri Hita Karanaâ€.